Meningkatkan Berpikir Kritis dengan Model Pbl, Tai, dan Talking Stick Siswa Kelas IV SD - Helda Elisa; Tika Puspita Widya Rini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The problem faced in the study is the lack of learning activity levels that affect student learning outcomes. This is due to learning that has not focused on student activity, lack of student participation in expressing opinions, and lack of understanding of the concept of the subject matter. To overcome this problem, Problem Based Learning, Team Assisted Individually, and Talking Stick models were applied. The objectives of this study were to measure teacher activity, increase student activity, develop critical thinking skills, and improve student learning outcomes. This study used a type of classroom action research with 22 students. Data analysis was done by cross tabulation method. The results of the study proved that there was an increase in each meeting from teacher activity which increased with the criteria of "Very Good", student activity obtained the criteria of "All Students are Very Active" with a percentage of 100% and improved critical thinking skills and student learning outcomes individually and classically. This shows that the Problem Based Learning, Team Assisted Individually, and Talking Stick models can improve students' activities, critical thinking skills, and learning outcomes. Abstract ditulis dalam bahasa Inggris dan bahasa Indonesia (kecuali artikel yang ditulis dalam bahasa Inggris) yang berisikan isu-isu pokok, tujuan penelitian, metode/pendekatan dan hasil penelitian. Abstrak ditulis dalam dua bahasa yaitu Bahasa Inggris dan Bahasa Indonesia, maksimal 200 kata dalam bahasa Inggrisdan150 kata dalam bahasa Indonesia. Abstrak ditulis dengan Times New Roman9, spasi 1, bercetak lurus dan dengan format satu kolom. (Times New Roman 9, spasi tunggal, dan cetak miring), maksimal 1 halaman.